ARDUINO-BASED SOLAR WATER PUMP MOTOR CONTROL TO ADJUST WATER CIRCULATION IN HYDROPONIC PLANTS - Sagita Rochman; Danu Krama (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2023)
Hydroponic plants are currently very popular because they do not require large land and land. By planting hydroponically, the harvest will be faster but it is necessary to pay attention to the air that is maintained, the purpose of distributing plant root nutrients, the use of solar power as a driving force for DC (Direct Current) water pumps in hydroponics is designed using several tools including: photovoltaic 10 Wp type polycrystalline, solar charge controller, 12v 5Ah battery, Arduino UNO, Dsi8b20 temperature sensor and 12V DC water pump. In this study, the author will make a solar pump motor drive (Solar Panel) and regulate the circulation of air volume and temperature in the hydroponic plant.